Improving Mathematics Learning Outcomes in Adding Fractions Material Through an Active Student Learning Model in Class VII SMP Negeri 1 Batang Onang Batang Onang District 2022 – 2023 Academic Year - Harahap, Masrawati (EDUCTUM: Journal Research, 2023)
This research was conducted in Class VII of SMP Negeri 1 Batang Onang. Batang Onang District. This type of research is classroom action research using an active student learning model which aims to determine the extent to which the use of an active student learning model can improve student learning outcomes in the material of adding fractions. The subjects of this research were class VII students at SMP Negeri 1 Batang Onang, with a total of 15 students consisting of 7 girls and 8 boys. From the research carried out, an increase in learning outcomes was obtained where after the action was carried out, the results of the research at the time the pre-cycle was carried out showed that the total score was 587, the average score was 39.1 with the minimum completeness criteria being 65, the percentage of classics that were completed was 20%, and the percentage of classics that had not yet been completed. completed 80%, and the highest score was 87, the lowest score was 25. Then in the implementation of cycle I the total score became 1072, the average student score increased to 71.5 with the percentage of classical completed being 60% and those not yet completed being 40%, and the highest score to 100, the lowest value to 50. Furthermore, after improvements were made, in cycle II the total score became 1295, the average score of students increased to 86, the percentage of completeness became 80% and 20% incomplete with the highest score remaining 100. From the learning results obtained by students, it can be concluded that the use of Active student learning models can improve student learning outcomes in mathematics subjects, especially in adding fractions